Blocking the Farnesyl Pocket of PDEδ Reduces Rheb-Dependent mTORC1 Activation and Survival of Tsc2-Null Cells - Armijo, Marisol Estrella; Escalona, Emilia; Peña, Daniela; Farias, Alejandro; Morin, Violeta; Baumann, Matthias; Klebl, Bert Matthias; Pincheira, Roxana; Castro, Ariel Fernando (Frontiers in Pharmacology, 2022)
Rheb is a small GTPase member of the Ras superfamily and an activator of mTORC1, a protein complex master regulator of cell metabolism, growth, and proliferation. Rheb/mTORC1 pathway is hyperactivated in proliferative diseases, such as Tuberous Sclerosis Complex syndrome and cancer. Therefore, targeting Rheb-dependent signaling is a rational strategy for developing new drug therapies. Rheb activates mTORC1 in the cytosolic surface of lysosomal membranes. Rheb's farnesylation allows its anchorage on membranes, while its proper localization depends on the prenyl‐binding chaperone PDE𝛿. Recently, the use of PDE𝛿 inhibitors has been proposed as anticancer agents because they interrupted KRas signaling leading to antiproliferative effects in KRas‐dependent pancreatic cancer cells. However, the effect of PDE𝛿 inhibition on the Rheb/mTORC1 pathway has been poorly investigated. Here, we evaluated the impact of a new PDE𝛿 inhibitor, called Deltasonamide 1, in Tsc2-null MEFs, a Rheb-dependent overactivated mTORC1 cell line. By using a yeast two-hybrid assay, we first validated that Deltasonamide 1 disrupts Rheb-PDE𝛿 interaction. Accordingly, we found that Deltasonamide 1 reduces mTORC1 targets activation. In addition, our results showed that Deltasonamide 1 has antiproliferative and cytotoxic effects on Tsc2-null MEFs but has less effect on Tsc2-wild type MEFs viability. This work proposes the pharmacological PDE𝛿 inhibition as a new approach to target the abnormal Rheb/mTORC1 activation in Tuberous Sclerosis Complex cells.